ANALISIS PENGEMBANGAN USAHA DISTRIBUTOR AIR MINERAL TOKO MEKAR SARI DI KOTA SURABAYA DENGAN STRATEGI SWOT - Trinita Kartika Andini; Yulyar Kartika Wijayanti; Nekky Rahmiyati; Mohammad Suyanto (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The purpose of this study was to delves into the strategic analysis of mineral water distributor business development. It uses the framework of SWOT (Strengths, Weaknesses, Opportunities, and Threats) to assess its impact on the company's progress This research aims to identify the inherent strengths and weaknesses of mineral water distribution businesses. It also aims to identify external opportunities and threats in operational environments. This is done through a thorough review of existing literature and data collection. By employing the SWOT analysis methodology, the study endeavors to uncover critical strategic insights pivotal for enhancing business progression, market positioning, and overall sustainability. The results of this study should not only add to the body of knowledge on strategic management in the mineral water distribution sector but also provide useful information for practitioners in the field, decision-makers in government, and other interested parties. This project aims to promote informed decision-making, innovation, and sustainable company development and growth within the mineral water distribution industry by improving knowledge of strategic decision-making processes in this environment.